Naming the witch, housing the witch and living with witchcraft: an ethnography of ordinary lives in Northern Ghana's witch camps - Mutaru, Saibu (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.